PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Tasya Andhita Septiani; Tri Siswantini; Sri Murtatik (Jurnal Apresiasi Ekonomi, 2021)
This research is quantitative research that aims among other things to determine the effect of liquidity, leverage and profitability of the financial distress. The sample in the consumer goods industry this research in the listed in Indonesia Stock Exchange period 2016 - 2018. The sampling technique used in this research is purposive sampling method. The research sample of 24 companies with a total number of observations 53. Testing the hypothesis in this study using logistic regression analysis with Eviews 9.0 program. The results of the test were obtained (1) there is a significant effect on the liquidity of financial distress, (2) there is no effect on the leverage of financial distress, (3) there is a significant effect on the profitability of financial distress